Preparation method of low-dimensional torsion angle material energy storage device and application thereof

CN122930730APending Publication Date: 2026-10-16UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510441443.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明涉及一种用于低维扭角材料储能器的制备方法及其应用,以解决现有储能技术中存在的低能量密度和高能量损耗的问题

Benefits of technology

[0039] 1. The low-dimensional twisted-angle material energy storage device of the present invention can effectively overcome the shortcomings of low release efficiency and low energy density of traditional dielectric energy storage devices. Its energy storage performance is significantly better than that of conventional traditional dielectric materials and other layered ferroelectric thin film materials, while also possessing good stability in the working environment. The low-dimensional twisted-angle energy storage material of the present invention expands the energy storage applications of dielectric materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930730A_ABST
    Figure CN122930730A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of low-dimensional twist angle material energy storage, by one or more layered materials with specific twist angle θ Stack to form van der waals heterostructure, the nanoscale periodicity moore superlattice is formed at the interface of the heterostructure;The twist angle θ Range is 0-15 °, and the layered material is formed using homogeneous angle stacking or gradient angle stacking between each other.The low-dimensional twist angle material energy storage of the present application can effectively overcome the shortcomings of high loss and low energy density of dielectric energy storage, and the energy storage performance is obviously superior to conventional dielectric material and other layered ferroelectric thin film material, and simultaneously has good working environment stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dielectric energy storage, and specifically relates to a method for preparing a low-dimensional twisted corner material energy storage device and its application, as well as an efficient energy storage method for achieving multiple interface accumulation using low-dimensional twisted corner materials. Background Technology

[0002] With the growing demand for high-performance storage solutions in fields such as the Internet of Things (IoT), Artificial Intelligence (AI), and mobile devices, dielectric energy storage devices have attracted widespread attention due to their superior performance and potential application prospects. Compared with electrochemical energy storage technologies, electrostatic energy storage based on dielectric capacitors is the best enabler of fast charge-discharge speeds (microseconds) and high power density. Dielectric capacitors play an increasingly important role in electronic devices and power systems. However, the relatively low energy density of dielectric capacitors hinders their wider application. Currently, much effort is focused on developing reliable and efficient dielectrics with higher energy densities.

[0003] Dielectric energy storage capacitors possess characteristics such as fast charging and discharging speeds, high power density, and strong voltage withstand capabilities, making them widely used in energy, power, and electronic circuit systems. Currently common dielectric ceramics include lead-based / lead-free bulk ceramics, multilayer ceramics, ceramic films, and glass ceramics. However, dielectric energy storage devices exhibit relatively low energy density and low release efficiency, thus limiting their industrial applications to some extent. Therefore, developing dielectric materials with high energy density and high release efficiency is a current frontier and hot topic in materials science research.

[0004] Although previous studies have shown that relaxor ferroelectric thin films with nano-ferroelectric domain structures are among the most promising material systems, achieving ~100 J / cm², 3 The energy storage density and energy storage efficiency are 60-80%. However, losses caused by the domain switching barrier limit further improvements in related energy storage performance. Furthermore, composite materials such as polymer thin films, inorganic / organic composites, core-shell structure fillers, and multilayer structures cannot meet the requirements of actual industrial production due to complex processes and poor mechanical properties. Therefore, there is an urgent need for a novel, highly efficient energy storage mechanism and a material with high energy storage density. Summary of the Invention

[0005] This invention relates to a method for fabricating low-dimensional twisted-angle material energy storage devices and their applications, aiming to address the problems of low energy density and high energy loss in existing energy storage technologies. Twisted-angle materials possess moiré superlattices, which can effectively control the band structure and interlayer polarization charge distribution. Moiré superlattices can induce changes in the electronic structure and band transitions of the material, thereby generating novel quantum phenomena. Currently, twisted-angle materials are commonly used in semiconductor devices, optical devices, catalysts, and high-sensitivity sensors; however, their application in dielectric energy storage (or capacitor energy storage) has not been explored or researched. This invention is the first to propose a new feasible solution for developing high-performance dielectric energy storage technology by applying twisted-angle materials to the field of dielectric energy storage and optimizing their related performance.

[0006] In a first aspect, the present invention provides a low-dimensional twisted material energy storage device, which is formed by stacking one or more layered materials at a specific twist angle θ to form a van der Waals heterostructure. A nanoscale periodic moiré superlattice (lattice constant λ = 10-500 nm, uniformity deviation ≤ ±5%) is formed at the interface of the heterostructure. The moiré superlattice generates a bistable polarization effect, so that the energy storage efficiency of the energy storage device is ≥90%.

[0007] Furthermore, the torsion angle θ ranges from 0 to 15° and satisfies one of the following conditions: (a) Homogeneous angle stacking: the interfaces of all layered materials maintain the same torsion angle θ; (b) Gradient angle stacking: the torsion angles of adjacent layered material interfaces increase in steps of Δθ = 0.1-5°, forming θ1 < θ2 < ... < θ N An angle sequence (N is the number of layers, N≥2) is used to achieve cumulative gain of polarization states. Preferably, the torsion angle θ ranges from 1° to 5°; Δθ = 0.1° to 1°.

[0008] The torsion angles described in this invention are all calculated in the same direction. For example, the layered materials are stacked clockwise with homogeneous or gradient angles; or the layered materials are stacked counterclockwise with homogeneous or gradient angles (e.g.) Figure 1 (As shown).

[0009] The layered material is selected from at least one of the following: transition metal chalcogenides (MoS2, WS2), elemental monolayer materials (graphene, black phosphorus), boron nitride (h-BN), Sb2O3, MXenes (Ti3C2Tx).

[0010] Preferably, the layered material comprises at least one layer of boron nitride (h-BN).

[0011] Furthermore, the lateral extension dimension of the low-dimensional material energy storage device is 1μm-1m, preferably 100μm-1m, which can be adapted to chip-level to industrial-grade energy storage devices.

[0012] Furthermore, the low-dimensional material energy storage device has 2-10,000 stacked layers to meet the flexibility of different energy storage needs. Preferably, the number of stacked layers is 2-10 layers, more preferably, the number of stacked layers is 2-6 layers.

[0013] The thickness of the layered material is 0.2-20 nm, preferably 0.5-10 nm.

[0014] Secondly, the present invention provides a method for preparing the above-mentioned low-dimensional twisted material energy storage device, including dry point transfer, wet face-to-face transfer, solution method, evaporation method, and chemical vapor deposition.

[0015] Preferably, the present invention employs a dry point transfer method, comprising the following steps:

[0016] 1) Substrate pretreatment: The substrate material is subjected to plasma or vacuum annealing to enhance surface hydrophilicity and cleanliness.

[0017] Furthermore, the substrate material is a silicon wafer or a silicon oxide substrate material.

[0018] Furthermore, the plasma treatment conditions are: power 40-50W, Ar / O2 mixed gas (volume ratio 9:1), and treatment time 5-10 minutes.

[0019] Furthermore, the vacuum annealing treatment refers to annealing in a vacuum annealing furnace by introducing a mixed gas of H2 / Ar (volume ratio 1:9) at 800-900°C for 1-2 hours.

[0020] 2) The layered material is peeled off from the substrate or growth substrate by mechanical exfoliation or wet chemical etching: For example, the layered material crystal is repeatedly peeled off by transparent tape to obtain layered nanosheets.

[0021] Specifically, it includes the following steps:

[0022] 2.1 Mechanical exfoliation: Layered material crystals are sandwiched between two layers of transparent tape, and layered nanosheets are gradually obtained through 10-30 cycles of exfoliation (ambient temperature 25±1℃, exfoliation rate 0.5mm / s).

[0023] 2.2 Using polydimethylsiloxane (PDMS) assisted transfer or polymethyl methacrylate (PMMA) assisted transfer, the tape with the target layered nanosheets attached is adhered to the pre-stretched polydimethylsiloxane PDMS or PMMA elastic film substrate; the tape is removed, and the layered material is left on the PDMS or PMMA film by means of the van der Waals force between the PDMS / PMMA and the layered nanosheets.

[0024] Furthermore, the layered materials can be of the same type or different types. When different types of multidimensional materials are used, other layered materials can also be prepared by mechanical exfoliation.

[0025] Optionally, it also includes: 2.3 Directional cleavage and orientation maintenance step: breaking the layered material into one or more subunits with consistent orientation along a specific lattice direction. This step is more suitable for layered materials of the same material, utilizing the van der Waals adsorption energy at the interface between PDMS / PMMA and the layered material to maintain the atomic-level flatness of the fracture surface, forming a stacked precursor with a strictly coherent crystal orientation, whose relative twist angle can be precisely set by a subsequent rotation angle control module.

[0026] 3) Dry-type point transfer: Stack the layered materials sequentially according to the torsion angle θ between the layered materials.

[0027] 3.1 Initial layer transfer: The first layered material is bonded to the substrate using a PDMS or PMMA membrane and pre-fixed under nitrogen atmosphere with a pressure of 0.1-0.5 MPa;

[0028] 3.2 A continuous twisted heterostructure was constructed using a layer-by-layer rotational assembly method:

[0029] 3.2.1 Control the torsion angle θ between each layer of material and the previous layer of material, and use a positioning stage to generate van der Waals forces between the material layers to complete the stacking of layered materials and form a continuous torsional heterostructure; the relative lattice orientation can be monitored in real time using a laser interferometer (wavelength 632.8nm);

[0030] Furthermore, the torsion angle of each subsequent layer of material relative to the previous layer is controlled to increase by a step size of Δθ = 0.1-5°. After every N layers are stacked, the torsion angle satisfies θ. N =θ1+(N-1)Δθ.

[0031] The thickness of each layered material is 0.2-20 nm.

[0032] 3.2.2 Hot pressing bonding: Hot pressing bonding is performed at a pressure of 0.1-1MPa and a temperature of 80-120℃ for 1-40 minutes.

[0033] Furthermore, the present invention performs hot-press bonding under gradient pressure conditions: first, hot-press bonding is performed at a pressure of 0.1-0.5 MPa (excluding) and a temperature of 80-120℃ for 1-20 minutes, and then hot-press bonding is performed at a pressure of 0.5-1 MPa and a temperature of 80-120℃ for 1-20 minutes.

[0034] By controlling different pressures, the angular drift caused by thermal expansion can be compensated, reducing angular errors; moreover, the interface can be optimized, the interface defect density reduced, and the cycle stability of the energy storage device maintained.

[0035] 4) Annealing treatment: Heat to 160-180℃ at 5-10℃ / min, then rapidly cool to -40~-50℃, and then heat to room temperature at 1-5℃ / min.

[0036] Furthermore, the actual angular sequence θ1, θ2, ..., θ was measured by selected area electron diffraction (SAED). N To verify the angle θ N =θ1+(N-1)Δθ.

[0037] Thirdly, this invention provides a low-dimensional twisted-angle material energy storage device as described in the first aspect or a low-dimensional twisted-angle material energy storage device prepared through the second aspect, for use in the field of dielectric energy storage, enabling efficient energy storage mechanisms and energy density. The low-dimensional twisted-angle material energy storage device is mainly composed of one or more layered low-dimensional materials stacked vertically at a certain twist angle. This twist angle is used to obtain a polarized bistable nanoscale domain structure, thereby achieving low energy loss and high power density. In this nanodomain structure, two polarization states are formed, thus achieving a cumulative positive ionization effect across multiple interfaces, thereby achieving high energy density. The low-dimensional twisted-angle energy storage material of this invention expands the energy storage applications of dielectric materials and is suitable for high-energy-density batteries, capacitors, and other energy storage devices.

[0038] The beneficial effects of this invention are:

[0039] 1. The low-dimensional twisted-angle material energy storage device of the present invention can effectively overcome the shortcomings of low release efficiency and low energy density of traditional dielectric energy storage devices. Its energy storage performance is significantly better than that of conventional traditional dielectric materials and other layered ferroelectric thin film materials, while also possessing good stability in the working environment. The low-dimensional twisted-angle energy storage material of the present invention expands the energy storage applications of dielectric materials.

[0040] 2. The low-dimensional twisted-angle material energy storage device provided by this invention introduces the cumulative polarization effect brought about by the molar nanodomain structure, which has the advantages of fast charging and discharging speed, high power density, strong withstand voltage, and low energy loss. It also features miniaturization and multifunctionality. Furthermore, the preparation process of this invention is simple and low-cost, and it achieves controllable angle of the low-dimensional material, which is conducive to further development of applications of twisted-angle low-dimensional materials and large-scale practical application production in the energy storage field.

[0041] 3. This invention constructs a low-dimensional van der Waals heterostructure with a continuous angular gradient arrangement. By controlling the angle, it enables adjacent material layers to form an interlayer structure with θ1 < θ2 < ... < θ. NThe increasing gradient distribution reduces the interlayer lattice mismatch, thereby reducing the defect density in the moiré fringe region. This invention pioneers an angle gradient increasing configuration that breaks through the traditional single torsion angle limitation, resulting in the release of interfacial stress and band synergy; through the synergistic design of Δθ and the number of layers N, continuous tuning of the moiré superlattice is achieved, thus endowing the material with superior energy efficiency and energy density.

[0042] 4. By employing hot-press bonding processes with different pressures, this invention can compensate for angular drift caused by thermal expansion, reduce angular errors, optimize interface performance, reduce interface defect density, achieve stable directional stacking and precise angle control, and improve the overall performance of low-dimensional twisted materials. Attached Figure Description

[0043] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0044] Figure 1 Example 1: Schematic diagram of the atomic structure of twisted boron nitride (t-hBN);

[0045] Figure 2 Hysteresis loops of twisted boron nitride (t-hBN) in Example 1 (red) and Comparative Example 1 (blue);

[0046] Figure 3 Example 1: Optical microscope image of twisted boron nitride (t-hBN). Detailed Implementation

[0047] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0048] Example 1

[0049] This invention provides a twisted hexagonal boron nitride (t-hBN) thin film material for energy storage. This low-dimensional dielectric material allows for control of energy storage efficiency by adjusting the twist angle. The low-dimensional twisted dielectric material is prepared by stacking two hexagonal boron nitride (hBN) nanosheets at a 1° angle; this angle is calculated based on the angle between the crystal orientations of the two nanosheets.

[0050] The method for preparing the above-mentioned low-dimensional twisted material t-hBN includes the following steps:

[0051] Step 1) Substrate pretreatment:

[0052] Select silicon wafer substrate material with a surface flatness ≤0.1nm and perform plasma treatment (power 50W, Ar / O2 mixed gas 9:1, treatment time 10 minutes) to enhance surface hydrophilicity.

[0053] 2) Mechanically peel off the layered material:

[0054] 2.1 Mechanical peeling: Prepare an ultrathin boron nitride crystal (2mm in size), attach the ultrathin boron nitride (hBN) crystal between two layers of transparent tape; repeatedly stick and peel the tape to peel off the crystal, making it into a thinner layered nanosheet;

[0055] 2.2 PDMS-assisted transfer: Adhesive tape with attached hBN layered nanosheets is attached to a pre-stretched polydimethylsiloxane PDMS elastic substrate; the tape is removed, and the layered material is left on the PDMS film by means of the van der Waals force between PDMS and hBN;

[0056] 2.3 Directional splitting and orientation retention: The layered nanosheets were broken into two subunits with the same orientation along a specific lattice direction. These were used as two samples of the twisted material t-hBN stacked on top of each other. The two nanosheets had the same crystal orientation, which made it easy to determine the twist angle.

[0057] 3) Fixed-point transfer:

[0058] 3.1 Initial layer transfer: The first hBN layered nanosheets were bonded to the substrate through a PDMS film and pre-fixed under nitrogen atmosphere with a pressure of 0.5 MPa;

[0059] 3.2 A continuous torsional heterostructure was constructed using a layer-by-layer rotational assembly method:

[0060] 3.2.1 Align the second hBN layered nanosheet with the first hBN layered nanosheet according to the preset torsion angle θ1 = 1°, and use the positioning stage to generate van der Waals forces between the material layers;

[0061] 3.2.2 Hot pressing bonding: First, hot pressing bonding is performed at a pressure of 0.3 MPa and a temperature of 100℃ for 5 min, and then hot pressing bonding is performed at a pressure of 1 MPa and a temperature of 100℃ for 5 min.

[0062] 4) Annealing treatment: The temperature is raised to 160℃ at 5℃ / min and then rapidly cooled to -50℃. Then, the temperature is raised to room temperature at 5℃ / min to separate the layered material from the substrate silicon wafer, thereby realizing the preparation of t-hBN.

[0063] from Figure 3As can be seen, the two hBN layered nanosheets are stacked at 1° to each other, forming the low-dimensional twisted angle material energy storage device of the present invention.

[0064] Example 2

[0065] Following the method of Example 1, without the directional pyrolysis and orientation retention step 2.3, low-dimensional twisted angle material energy storage devices of different materials were prepared, wherein monolayer hexagonal boron nitride (hBN) and monolayer graphene were stacked at 1° to each other.

[0066] Example 3

[0067] The other steps are the same as in Example 1, except that:

[0068] 3.1 Initial layer transfer: The first hBN layered nanosheets were bonded to the substrate through a PDMS film and pre-fixed under nitrogen atmosphere with a pressure of 0.5 MPa;

[0069] 3.2 A continuous twisted heterostructure was constructed using a layer-by-layer rotational assembly method:

[0070] 3.2.1 Align the second hBN layered nanosheet with the first hBN layered nanosheet (twist angle θ1 = 5°) and use a positioning stage to generate van der Waals forces between the material layers; further align the third hBN layered nanosheet with the second hBN layered nanosheet (twist angle θ2 = 5°) and use a positioning stage to generate van der Waals forces between the material layers, thus completing the stacking of each hBN layered nanosheet.

[0071] 3.2.2 Hot-press bonding: First, hot-press bonding was performed at a pressure of 0.3 MPa and a temperature of 100 °C for 5 min, followed by hot-press bonding at a pressure of 1 MPa and a temperature of 100 °C for 5 min. This resulted in a low-dimensional twisted-angle energy storage device, t-hBN, consisting of three layered hBN nanosheets stacked at a 5° angle to each other.

[0072] Example 4

[0073] The other steps are the same as in Example 1, except that:

[0074] 3.1 Initial layer transfer: The first hBN layered nanosheets were bonded to the substrate through a PDMS film and pre-fixed under nitrogen atmosphere with a pressure of 0.5 MPa;

[0075] 3.2 A multilayer torsion hBN heterostructure was constructed using a layer-by-layer rotational assembly technique:

[0076] 3.2.1 Using a positioning stage, the second hBN layered nanosheet is aligned with the first layered nanosheet at a twist angle of θ1 = 1° to achieve heterogeneous stacking. Subsequently, the relative twist angle θ2 = 1.2° of the third hBN layered nanosheet with respect to the second layered nanosheet is adjusted in increments of Δθ = 0.2° to achieve precise stacking of the third layered nanosheet. Finally, a low-dimensional twisted angle material energy storage device t-hBN is obtained, in which three hBN layered nanosheets are stacked sequentially at 1° and 1.2°.

[0077] Example 5

[0078] The other steps are the same as in Example 3, except that the stacking angle of each layer of hexagonal boron nitride is controlled to finally form a low-dimensional twisted angle material energy storage device t-hBN with three hexagonal boron nitride (hBN) nanosheets stacked at 3° to each other.

[0079] Example 6

[0080] The other steps are the same as in Example 5, except that the stacking angle of the three hBN nanosheets increases in sequence.

[0081] 3.1 Initial layer transfer: The first hBN layered nanosheets were bonded to the substrate through a PDMS film and pre-fixed under nitrogen atmosphere with a pressure of 0.5 MPa;

[0082] 3.2 Multilayer hBN heterostructures were constructed using a layer-by-layer rotational assembly technique:

[0083] 3.2.1 The second hBN layered nanosheet was aligned with the first layered nanosheet with a torsion angle of θ1 = 3° using a positioning stage to complete heterogeneous stacking; then, the relative torsion angle θ2 = 3.8° of the third layered nanosheet with respect to the second layered nanosheet was adjusted with an incremental step size of Δθ = 0.8° to achieve precise stacking of the third hBN layered nanosheet.

[0084] Ultimately, a low-dimensional twisted-angle material energy storage device, t-hBN, was obtained, consisting of three layered hBN nanosheets stacked sequentially at 3° and 3.8°.

[0085] Example 7

[0086] The other steps are the same as in Example 3, except that gradient pressure hot-press bonding process is not used.

[0087] 3.2.2 Hot-press bonding: Hot-press bonding was performed at a constant pressure of 1 MPa and a temperature of 100℃ for 10 min. This resulted in a low-dimensional twisted-angle energy storage device, t-hBN, consisting of three layered hBN nanosheets stacked at a 5° angle to each other.

[0088] Example 8

[0089] The other steps are the same as in Example 1, except that the stacking angle of the four layered nanosheets increases.

[0090] 3.1 Initial layer transfer: The first hBN layered nanosheets were bonded to the substrate through a PDMS film and pre-fixed under nitrogen atmosphere with a pressure of 0.5 MPa;

[0091] 3.2 Multilayer hBN heterostructures were constructed using a layer-by-layer rotational assembly technique:

[0092] 3.2.1 First, the second hBN layered nanosheet is aligned with the first layered nanosheet with a twist angle of θ1 = 1° using a positioning stage to complete heterogeneous stacking; then, the relative twist angle of the third layered nanosheet with respect to the second layered nanosheet is adjusted to θ2 = 1.5° with an incremental step size of Δθ = 0.5° to achieve precise stacking of the third layer; continuing with this process parameter, the twist angle of the fourth hBN nanosheet is adjusted to θ3 = 2° to complete the assembly.

[0093] Finally, a low-dimensional twisted-angle material energy storage device t-hBN was obtained, consisting of four hBN layered nanosheets stacked sequentially at 1°, 1.5°, and 2°.

[0094] Comparative Example 1: Conventional Nanosheets

[0095] The other steps are the same as in Example 1, except that there is only one nanosheet, and the thickness of the nanosheet is exactly twice that of the twisted nanosheet, forming a conventional low-dimensional material energy storage device.

[0096] Performance testing:

[0097] The main evaluation parameters for dielectric energy storage devices include recoverable energy density (Wrec), energy efficiency (η), breakdown strength (Eb), thermal stability, and fatigue durability. Energy density is a parameter that measures the energy storage capacity of an energy storage device. As can be seen from the formula for energy density, the energy density of a dielectric capacitor can be obtained by the area enclosed by the polarization-electric field (PE) curve and the polarization axis. In the PE hysteresis loop of the dielectric material, the areas enclosed by the charging, discharging, and charge-discharge curves and the polarization axis represent the total energy density (Ws), the released energy density (Wrec), and the lost energy density (Wloss), respectively. Energy release efficiency (η) is a key indicator for measuring the energy utilization efficiency of an energy storage device. In dielectric capacitors, its value can be calculated using the following formula:

[0098] η = W rec / W s *100%

[0099] In the PE hysteresis loop of the dielectric material, the areas enclosed by the charging, discharging, and charge-discharge curves and the polarization axis represent the total energy density (Ws), released energy density (Wrec), and lost energy density (Wloss) of the device, respectively, and the storage efficiency η is calculated.

[0100] The PE hysteresis loops of the materials in each embodiment and comparative example were tested under normal temperature and pressure conditions.

[0101] The hysteresis loop is an important graph describing the polarization characteristics of a material under the influence of an electric field. It is commonly used to study dielectrics, ferromagnetic materials, and other materials with hysteresis effects. The hysteresis loop shows the relationship between the electric field strength (E) and the polarization intensity (P) or current (I), and is an important tool for understanding the behavior of materials under an applied electric field. By analyzing the hysteresis loop, important information about the material's properties, stability, and application potential can be obtained.

[0102] Figure 2 In the hysteresis loop, the area of ​​the yellow region (representing the released energy density Wrec) enclosed by the charging, discharging, and charge-discharging curves of the twisted angle material energy storage device of Example 1 and the polarization axis is significantly larger than the area of ​​the green region formed by the conventional hexagonal boron nitride material of Comparative Example 1. This indicates that the energy storage performance of Example 1 of the present invention is significantly better than that of the conventional hexagonal boron nitride of Comparative Example 1.

[0103] Although the efficiency of Example 1 is slightly lower than that of Comparative Example 1, the energy density of the two differs significantly, with Example 1 being more than three times that of Comparative Example 1. Furthermore, Example 1 boasts an energy release efficiency as high as 95.7%, demonstrating a clear technical advantage. It effectively overcomes the drawbacks of low energy density and high energy loss, achieving a balance between the two aspects of technical performance. In addition, the Ws, Wrec, and η results for each example and comparative example are shown in Table 1.

[0104] Table 1

[0105]

[0106] Examples 1 and 4, and Examples 5 and 6 show that the boron nitride (hBN) materials in each layer exhibit a certain stacking increasing angle, which has a certain effect on simultaneously improving energy density and efficiency.

[0107] As can be seen from Examples 3 and 7, the gradient pressure bonding process can compensate for the angular drift caused by thermal expansion, optimize interface performance, and improve the stability of twisted materials, thereby improving the efficiency of storage materials.

[0108] In summary, the twisted material prepared in the embodiments of the present invention, compared with the comparative examples and other layered materials, can control the energy storage efficiency by controlling the twist angle, has a high energy density Ws and efficiency η, low energy loss, and good working environment stability.

[0109] The above-described embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and are not intended to limit it. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the scope of the technology disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of protection of the claims.

Claims

1. A low-dimensional twisted-angle material energy storage device, characterized in that, A van der Waals heterostructure is formed by stacking one or more layered materials at a specific twist angle θ, and a nanoscale periodic moiré superlattice is formed at the interface of the heterostructure; the twist angle θ ranges from 0 to 15°, and the layered materials are stacked with homogeneous angles or gradient angles.

2. The low-dimensional twisted material energy storage device according to claim 1, characterized in that, The homogeneous angle refers to the fact that all layered materials maintain the same torsion angle θ at their interfaces; the gradient angle refers to the fact that the torsion angle θ of adjacent layered materials interfaces is different, and increases in increments of Δθ = 0.1-5°, forming θ1 < θ2 < ... < θ N The angle sequence, where N is the number of layers, and N≥2.

3. The low-dimensional twisted material energy storage device according to claim 1, characterized in that, The layered material is selected from at least one of the following: transition metal chalcogenides, graphene, black phosphorus, boron nitride, Sb2O3, and MXenes; The lateral extension dimension of the low-dimensional material energy storage device is 1μm-1m; The number of stacked layers of the low-dimensional material energy storage device is 2-10000 layers, preferably 2-10 layers; The thickness of the layered material is 0.2-20 nm.

4. The method for preparing the low-dimensional twisted material energy storage device according to any one of claims 1-3, comprising the following steps: 1) Substrate pretreatment: The substrate material is subjected to plasma or vacuum annealing to enhance surface hydrophilicity and cleanliness; 2) The layered material is peeled off from the substrate or growth substrate by mechanical exfoliation or wet chemical etching. 3) Dry point transfer: According to the torsion angle θ of the interface between adjacent layered materials, a continuous torsional heterostructure is constructed by a layer-by-layer rotational assembly method; 4) Annealing treatment: Heat to 160-180℃ at 5-10℃ / min, then rapidly cool to -40~-50℃, and then heat to room temperature at 1-5℃ / min.

5. The preparation method according to claim 4, characterized in that, Step 1) The substrate material is a silicon wafer or silicon oxide substrate material; the plasma treatment conditions are: power 40-50W, Ar / O2 mixed gas, treatment time 5-10 minutes; the vacuum annealing treatment is to introduce H2 / Ar mixed gas into a vacuum annealing furnace and anneal at 800-900℃ for 1-2 hours.

6. The preparation method according to claim 4, characterized in that, Step 2) includes mechanical stripping or wet chemical etching, polydimethylsiloxane (PDMS) or polymethyl methacrylate (PMMA) assisted transfer steps, and optionally, directional cleavage and orientation retention steps.

7. The preparation method according to claim 4, characterized in that, Step 3) include: 3.1 Initial layer transfer: The first layered material is bonded to the substrate using a PDMS or PMMA membrane and pre-fixed under nitrogen atmosphere with a pressure of 0.1-0.5 MPa; 3.2 A continuous torsional heterostructure was constructed using a layer-by-layer rotational assembly method: 3.2.1 Control the torsion angle θ between each layered material and the previous layered material to complete the stacking of layered materials and form a continuous torsional heterostructure; 3.2.2 Hot pressing bonding: Hot pressing bonding is performed at a pressure of 0.1-1MPa and a temperature of 80-120℃ for 1-40 minutes.

8. The preparation method according to claim 7, characterized in that, In step 3.2.1, the torsion angle of each layer of material relative to the previous layer is controlled to increase by Δθ = 0.1-5°. After every N layers are stacked, the torsion angle θ is... N =θ1+(N-1)Δθ.

9. The preparation method according to claim 7, characterized in that, In step 3.2.2, firstly, hot-press bonding is performed at a pressure of 0.1-0.5 MPa (excluding) and a temperature of 80-120℃ for 1-20 minutes, and then hot-press bonding is performed at a pressure of 0.5-1 MPa and a temperature of 80-120℃ for 1-20 minutes.

10. The low-dimensional twisted-angle material energy storage device according to any one of claims 1-3 or the low-dimensional twisted-angle material energy storage device obtained by the preparation method according to any one of claims 4-9, for use in the field of dielectric energy storage.